Analisis Hadits Ahkam Muamalah dalam Fatwa DSN MUI tentang Murâbahah, Salam dan Istishnâ’ - Muhammad Syarif Hidayatullah (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2020)
Murâbahah, salam and istishnâ' is a type of buying and selling that is currently known conceptually can be an option in the products of Islamic financial institutions. DSN-MUI as an institution that has authority in Islamic economic and finance fatwas has formulated a fatwa on these three types of buying and selling, where in the fatwa there are hadiths ahkam muamalah as the legal basis. This paper aims to analyze the hadiths ahkam muamalah in the fatwa DSN-MUI about murâbahah, salam and istishnâ' through the study of existence (takhrij hadith) and substance (study of meaning) hadith. Based on the analysis conducted, hadith ahkam muamalah in the fatwa DSN-MUI on murâbahah, salam and istishnâ', broadly explains the principle of sharia agreement (ar-ridha, al-ibâhah, al-mashlahah), blessings in the sale and purchase of cashless (classed as hadith dhaif in the category of hadith majhul), prohibition of delaying the payment of debts for the able, legality of buying and selling salam dan legality of advances in the sale and purchase (classed as hadith dhaif in the category of hadith mursal).